2016
DOI: 10.1073/pnas.1521738113
|View full text |Cite
|
Sign up to set email alerts
|

PROTAC-induced BET protein degradation as a therapy for castration-resistant prostate cancer

Abstract: Prostate cancer has the second highest incidence among cancers in men worldwide and is the second leading cause of cancer deaths of men in the United States. Although androgen deprivation can initially lead to remission, the disease often progresses to castration-resistant prostate cancer (CRPC), which is still reliant on androgen receptor (AR) signaling and is associated with a poor prognosis. Some success against CRPC has been achieved by drugs that target AR signaling, but secondary resistance invariably em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
654
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 680 publications
(698 citation statements)
references
References 45 publications
15
654
1
1
Order By: Relevance
“…One promising strategy undergoing clinical evaluation in CRPC is targeting BET family proteins (ClinicalTrials.gov identifier: NCT02711956, NCT03150056). Several BETi, and PROTAC induced BET protein degraders, have shown promising efficacy in preclinical models of CRPC, regulating AR signaling and AR-V7 expression (29,30,(33)(34)(35)(36). Although the mechanism by which BET inhibition regulates AR signaling is well described, the ability to regulate expression of AR-V7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One promising strategy undergoing clinical evaluation in CRPC is targeting BET family proteins (ClinicalTrials.gov identifier: NCT02711956, NCT03150056). Several BETi, and PROTAC induced BET protein degraders, have shown promising efficacy in preclinical models of CRPC, regulating AR signaling and AR-V7 expression (29,30,(33)(34)(35)(36). Although the mechanism by which BET inhibition regulates AR signaling is well described, the ability to regulate expression of AR-V7…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased BRD4 protein stability in substrate-binding adaptor speckle-type POZ protein (SPOP) mutant prostate cancers is associated with AR signaling (31,32). BET inhibitors (BETi) and proteolysis targeting chimera (PROTAC) induced BET protein degraders have anti-tumor activity in CRPC models (29,30,(33)(34)(35)(36), attenuating AR signaling and potently reducing C-MYC expression (29,30,33,34,36). More recently, BETi have been shown to decrease AR-V7 expression by regulating splicing factors required for its generation (30).…”
Section: Introductionmentioning
confidence: 99%
“…Cofactor inhibitors would have the hypothesized advantage that as they are "downstream" of AR, resistance cannot easily be brought about by upregulation of AR or its ligand, making the case for cofactor inhibitor use up-front in combination with traditional antiandrogens to enhance efficacy and block potential resistance mechanisms. Advances in technologies to interrogate chromatin have resulted in the identification of a number of essential AR coactivators and their proposal as potential drug targets (30,(42)(43)(44)(45). Historically, such cofactors and epigenetic regulators have proved notoriously difficult targets for the design of small-molecule inhibitors, hindering progress in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of this interaction with a small-molecule inhibitor of BRD4, JQ1, blocked AR chromatin association, transcriptional activity and AR-mediated PCa growth (Asangani et al 2014). More recently, a pan-BET degrader (based on PROTAC technology) was shown to have potent anti-CRPC activity (Raina et al 2016). Importantly, we and others have shown that BET inhibition has a dual mechanism of action, suppressing not only AR transcriptional activity but also AR gene transcription (Chan et al 2015, Raina et al 2016.…”
Section: Targeting Androgen Receptor Coregulatorsmentioning
confidence: 89%
“…More recently, a pan-BET degrader (based on PROTAC technology) was shown to have potent anti-CRPC activity (Raina et al 2016). Importantly, we and others have shown that BET inhibition has a dual mechanism of action, suppressing not only AR transcriptional activity but also AR gene transcription (Chan et al 2015, Raina et al 2016. This finding, combined with the mapping of the BRD4 interaction surface to the AR-NTD, suggests that BET inhibitors would have activity in CRPC driven by AR-LBD mutants and/or AR-Vs, a prediction that has been experimentally substantiated (Chan et al 2015, Asangani et al 2016, Raina et al 2016.…”
Section: Targeting Androgen Receptor Coregulatorsmentioning
confidence: 99%